A young persons guide to military service - Bradley, Jeff. (Massachusetts The Harvard Common Press, 1983)
This book should be highly recommended to young people considering military service. It contains a vast amount of information, objectively presenting the advantages and disadvantages of military life. Bradley raises issues of military philosophy and national policy as well as personal issues men and women need to consider in the decision-making process.
Keywords: Army